2014
DOI: 10.20533/ijcdse.2042.6364.2014.0246
|View full text |Cite
|
Sign up to set email alerts
|

Educating Leaders within the Context of an Inclusive Education Reform Agenda

Abstract: The quest for inclusive education necessitates a systemic process of initiating school reforms in order to create quality, participatory and socially just educational communities for learner diversity. Head teachers' role is considered as being crucial in this process, for they are expected to lead transformative changes to challenge the status quo, and to mobilize contextual struggles for the realization of an inclusive discourse. To this end, head teachers need to be afforded relevant professional developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The complexities surrounding the implementation of inclusive education have been well explored, and researchers have suggested that a combination of leadership styles and approaches may be needed to promote inclusive practices in schools (Futaba, 2016; Liasidou & Antoniou, 2014; Rayner, 2009; Sider et al, 2021). For instance, some studies have revealed that, to enhance inclusive practices, school leaders should perform three kinds of roles: transformational, transactional, and instructional (Poon-McBrayer, 2017b; Poon-McBrayer & Wong, 2013; Rayner, 2009; Urick, 2016; Urick & Bowers, 2014).…”
Section: Inclusive Education and Leadershipmentioning
confidence: 99%
See 3 more Smart Citations
“…The complexities surrounding the implementation of inclusive education have been well explored, and researchers have suggested that a combination of leadership styles and approaches may be needed to promote inclusive practices in schools (Futaba, 2016; Liasidou & Antoniou, 2014; Rayner, 2009; Sider et al, 2021). For instance, some studies have revealed that, to enhance inclusive practices, school leaders should perform three kinds of roles: transformational, transactional, and instructional (Poon-McBrayer, 2017b; Poon-McBrayer & Wong, 2013; Rayner, 2009; Urick, 2016; Urick & Bowers, 2014).…”
Section: Inclusive Education and Leadershipmentioning
confidence: 99%
“…However, the school leaders’ ability to support or supervise the implementation of inclusive education has also been questioned. Previous studies have reported that school leaders have expressed concerns over a lack of knowledge and inadequate pedagogical skills to support inclusive practices (Conrad & Brown, 2011; Liasidou & Antoniou, 2014, 2015). In a qualitative study exploring the effectiveness of inclusive practices in primary schools in Cyprus, Liasidou and Antoniou (2014) reported that principals did not have time to visit classrooms to observe whether and how teachers included students with disabilities, and they lacked the pedagogical skills necessary for inclusive practice.…”
Section: Inclusive Education and Leadershipmentioning
confidence: 99%
See 2 more Smart Citations